The impact of the pandemic of COVID-19 on child poverty in North Macedonia: Simulation-based estimates - Petreski, Marjan (Ревија за социјална политика/Journal of Social Policy, 2020)
The objective of this paper is to estimate the expected effects of the pandemic of Covid-19 for child poverty in North Macedonia. We rely on MK-MOD Tax & Benefit Microsimulation Model for North Macedonia based on the Survey on Income and Living Conditions 2019. The simulation takes into account the development of income, as per the observed developments in the first three quarters of 2020, derived from the Labor Force Survey, which incorporates the raw effect of the pandemic and the government response. In North Macedonia, almost no government measure directly aimed the income of children, however, three key and largest measures addressed household income: the wage subsidy of 14.500 MKD per worker in the hardest hit companies, relaxation of the criteria for obtaining the guaranteed minimum income, and one-off support to vulnerable groups of the population on two occasions. Results suggest that the relative child poverty rate is estimated to increase from 27.8 percent before the pandemic to 32.4 percent during the pandemic. This increase puts additional 19,000 children below the relative poverty threshold. Results further suggest that absolute poverty is likely to reduce primarily because of the automatic stabilizers in the case of social assistance and because of the one-time cash assistance.